(untitled) (Journal of actual problems of jurisprudence, 2018)
In work the legal analysis of public access to information in the field of environmental protection and use of natural resources in the Republic of Kazakhstan, discussed the place of norms of the legal institution, the legal bases of maintenance, realization and protection of the public’s right of access to environmental information. Public legal mechanism for regulation of public access to information in the field of environmental protection and use of natural resources, guarantee security and protection of environmental rights of man and citizen, as well as international law implementing regulatory impact on the public access to environmental information. Key words: environmental information, environmental protection, law, public access.